Indirect selection to 2-tridecanone content and its relation to tomato pinworm resistance - Labory, Claúdia Regina Gontijo; Cecília, Leniana Viana Costa Santa; Maluf, Wilson Roberto; Cardoso, Maria das Graças; Bearzoti, Eduardo; de Souza, João Cândido (Pesquisa Agropecuaria Brasileira, 1999)
This work had the objective to verify the relation between 2-tridecanone (2-TD) in selected plants and resistance level to tomato pinworm (Tuta absoluta (Meyrick, 1917) (Lepidoptera: Gelechiidae)) in advanced generations of Lycopersicon spp. interspecific crosses. It was used a tomato population (F4RC2 generation) segregant for 2-TD, a methyl ketone that controls the resistance of the tomato pinworm. Materials were selected and evaluated for a non-preference mechanism of resistance. Three genotypes with high level of the allelochemic 2-TD (HI1, HI2, HI3), two with low level (LO1, LO2) and two check genotypes were used. After a controlled infestation, oviposition preference, type and percent of leaflet damage, and damage index caused by the tomato pinworm were evaluated. Plants with high level of 2-TD (HI1, HI3) had a low progression of leaflet damage by Tuta absoluta. The LO1 genotype was much attacked by the tomato pinworm, while the LO2 genotype was accidentally attacked by acari of the Tetranychus genus, probably causing a dispute between the two arthropods. It was concluded that 2-TD high levels are associated to non-preference ovipositions and feeding resistance mechanisms to tomato pinworm.